Geometric Evaluation of Roads with UAV Technology Processed Through Orthophoto-Based Software on Jalan Soekarno Hatta Km 10 – Km 15 East Kalimantan - Dhinar Yoga Hanggung Legowo; Dhiana Dwi Widiawati; Angga Ridwan Sayid Mahendra (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2026)
This study evaluates the geometric conditions of the Soekarno-Hatta Poros Road KM 10–KM 15, East Kalimantan, utilizing Unmanned Aerial Vehicle (UAV) technology and Geodetic GPS as Ground Control Points (GCPs). Aerial photographic data were processed within Agisoft Metashape and subsequently analyzed based on the 2021 Bina Marga Road Geometric Design Guidelines. The processing of 1,732 images yielded high-quality orthophotos with a Ground Sample Distance (GSD) value of 3.56 cm/pixel. The model accuracy test produced a Circular Error 90% (CE90) of 0.0090 m and a Linear Error 90% (LE90) of 0.0101 m, thereby fulfilling the specifications for Class 1 Base Maps at a 1:1,000 Scale based on the Geospatial Information Agency (BIG) Regulation No. 6 of 2018. The horizontal alignment evaluation based on the 2021 Bina Marga regulation indicates that out of 34 Spiral-Circle-Spiral (S-C-S) type curves, 28 curves are declared as Not Meeting Requirements (TMS) due to significant transition curve overlap. Similarly, regarding the vertical alignment, a critical unsafe point was identified from STA 2+618 to STA 2+669 because the crest vertical curve is excessively short (L = 51.13 m, K = 9.70). These geometric non-conformities generate blind spots that restrict the stopping sight distance (SSD) within a speed variation of 20–70 km/h. It is recommended to perform phased reconstruction consisting of extending the straight tangent lengths, modifying the critical vertical curve dimensions, and adding road safety facilities.